Social Work Practice: Conundrums And Mitigations Among Tertiary Institutions in Rivers State (Genius Repository, 2023)
The paper investigates social work practice, its conundrums, and mitigations among tertiary institutions in Rivers State. Given this, the Structural functionalism theory of Talcott Parson (1961) was adopted to address these problems and develop interventions that aim to strengthen social structures and institutions to improve social work practice in Rivers State. Methodologically, the paper is a position paper therefore secondary sources/data were used for data collection. The thematic content analysis was adopted for the analysis of the secondary data collated. The study found conundrums affecting social work practices in tertiary institutions in Rivers State, including non-professional teaching of core social work courses in the tertiary institutions, lack of adequate resources/funding, poor working conditions, inadequate training and supervision, corruption, and political interference. We also found possible mitigations to address the above challenges. They include the need for increased funding and investment in social work practice in Rivers State and discouraging non-professional participation in the teaching of Social Work in the various tertiary institutions in Rivers State. In all, it was recommended among others that the executive and legislatures at the national levels, as well as the state levels, ensure the implementation of the 2017 social work bills, that was accented into law in 2022, to streamline the profession and avoid non-professionals in social work practices. This is achievable if some penalties are meted out to defaulters of the Social Work Act, or if the Nigerian Association of Social Work Educators (NASWE) and Nigerian Association of Social Workers (NASOW) are empowered to ensure that only professional social workers are practically involved in social work practices